2004
DOI: 10.1111/j.1326-6756.2004.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Australian Thysanoptera – biological diversity and a diversity of studies

Abstract: Studies in Australia on thrips have had extensive impacts worldwide. In behaviour, the latest definition of eusociality is derived from work on the radiation of thrips on Acacia species in central Australia, and these Acacia thrips also having been used to develop the concept of 'model clades' for analysing the evolution of behavioural and ecological diversity. In ecology, the concept of the lack of density dependent factors in population dynamics was elaborated through studies on the plague thrips of southern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…Although both sexes presented aggregation patterns, males were more aggregated than females and aggregations were mainly observed on the green plant parts, especially the leaves. Similar aggregation of males on terminal leaves were also observed in Pezothrips kellyanus Bagnall (Mound & Jackman, 1998; Mound, 2004; Navarro-Campos, 2013). However, previous reports on male aggregation of other thrips species indicated that it takes place mainly on the corolla of flowers (Kirk, 1985; Terry & Dyreson, 1996).…”
Section: Discussionsupporting
confidence: 67%
“…Although both sexes presented aggregation patterns, males were more aggregated than females and aggregations were mainly observed on the green plant parts, especially the leaves. Similar aggregation of males on terminal leaves were also observed in Pezothrips kellyanus Bagnall (Mound & Jackman, 1998; Mound, 2004; Navarro-Campos, 2013). However, previous reports on male aggregation of other thrips species indicated that it takes place mainly on the corolla of flowers (Kirk, 1985; Terry & Dyreson, 1996).…”
Section: Discussionsupporting
confidence: 67%
“…Proteaceae seem, for the main part, to have avoided insect associations. Majer et al (1997) estimated that there could be between 15,000 and 20,000 species of phytophagous insects on Eucalyptus in Australia, including members of Hemiptera (especially psylloids and coccoids), Coleoptera, Diptera, and Lepidoptera (Austin et al 2004), but there is a conspicuous paucity of Thysanoptera (Mound 2004). The Chrysomelinae (leaf beetles) demonstrate a radiation associated with eucalypts of some 750 species, but are virtually lacking on Proteaceae (C. A. M. Reid, personal communication).…”
Section: Australasian Insect Biodiversity -Overview and Special Elemementioning
confidence: 99%
“…When considering the Australian thrips fauna it is useful to distinguish between 'exotic' species that have entered Australia from the Americas or from the northern hemisphere since the arrival of Europeans, in contrast to 'adventive' species that are shared with south-east Asia and have possibly entered Australia over a longer period of time (Mound 2004). In this connection it should be noted that the number of Thripidae Sutherst et al (2004).…”
Section: Survey Results For C Fasciatusmentioning
confidence: 99%